TO STUDY EFFICACY OF COMPREHENSIVE DIABETES CARE (CDC) MANAGEMENT PROGRAM IN TYPE II DIABETIC OBESE PATIENTS: AN OBSERVATIONAL STUDY - Sane, Rohit M; Sabir, Imran A; Naik, Minal S; Shingan, Tejaswini; Mandole, *Rahul S (International Journal of Ayurveda and Pharma Research, 2018)
Context: Diabetes mellitus (DM) contributes to a major chunk of morbidity, mortality, and healthcare cost on a global level. The prevalence of DM is rising alarmingly, worldwide and India. Comprehensive Diabetes Care (CDC) is a combination of Panchakarma and diet management.Aims: This study was conducted to evaluate the effect of CDC on Glycosylated hemoglobin (HbA1c), body mass index (BMI), body weight, abdominal girth and dependency on conventional therapy in DM Patients.Setting and Design: This observational study was conducted in July 2017, wherein the data of obese Type II DM patients (HbA1c >6.5%) who attended out-patient departments (OPDs) at Madhavbaug clinics in Maharashtra, India were identified.Materials and Methods: Data of patients who were administered CDC (60-75 minutes) with minimum 6 sittings over 90 days (± 15 days) were considered. Variables were compared between day 1 and day 90 of CDC.Results: Out of 27 patients, 22 were included for analysis, out of which 10 were males while 12 females. CDC showed significant improvement in HbA1c 1.1% (from 8.80 ± 0.93 to 6.98 ± 1.73; p<0.001), BMI by 2.66 (from 33.79 ± 3.80 to 31.13 ± 3.91, p< 0.001), weight by 6.56 kg (from 83.67 ± 11.28 to 77.11 ± 12.27, p<0.001). Abdominal girth (from 104.34 ± 9.74 to 96.97 ± 11.93; p<0.001), also showed significant reduction. Dependency on concomitant medicines was reduced, with the number of patients on no concomitant medicines increasing from 27% to 41%.Conclusion: Comprehensive Diabetes Care Management Program found to be efficacious; by reducing HbA1c, as well as reducing dependency on allopathic medications.